O padrão de qualidade no Enade e o desempenho dos acadêmicos em três licenciaturas da UFMT : encontros e desencontros da educação superior - Santos, Leandro Elias dos (2022)
This research has at its theme the quality of higher education in the context of undergraduate courses in Biological Sciences, Physics, and Chemistry at the Federal University of Mato Grosso, Cuiabá Campus, where we sought to investigate the relationship between the ENADE results and the students’ performance in the year 2017 in Natural Sciences courses and the quality present in these courses through the students’ performance in the course and ENADE. Thus, the guiding question is as follows: what is the relationship between the ENADE results and the students’ performance, in 2017, in Natural Sciences courses at the Federal University of Mato Grosso, Cuiabá Campus, and the quality present in these courses? The definition of quality is complex, since it is a social-historical construct, and as the human race evolved it also gained new meanings and subjectivity. The definition of quality is multidimensional and, today, according to the policy of higher education evaluation, SINAES, it has been defined by indicators. ENADE evaluates the students at the end of their graduation path; in Higher Education Institutions, we have established the Performance Coefficient that shows the percentage of student performance at the end of the course, since the two indicators evaluate the same question: the learning acquired by the student during his academic path. The research has a qualitative approach, of an exploratory and documentary type, our research procedures involve bibliographical and documental analysis and interviews with the teachers of the structuring teaching center. To that end, we select three undergraduate courses and analyze these indicators together with the perception of course teachers, to understand the issue of quality in undergraduate courses in higher education, and to know if, in fact, the indicators reflect the reality of the evaluated courses, especially the distinct quality presented in these courses. As a result of the research, we highlight that it was evident among the interviewed teachers that the students’ performance in the course through the performance coefficient does not reflect the quality of the course, since the evaluation instruments of the curricular components are not effective in measuring the knowledge acquired by the students. In addition, the results of ENADE are important indicators, but it has weaknesses in its process, such as the test format, the questions, the way it has been handled in the participating courses, and the lack of commitment of some students – so it reflects the quality that the course has. Therefore, the perception of quality presented by the subjects about the courses is directly connected to the formative process: as the qualified teaching staff, solid training to the future teachers, providing opportunities for formative experiences through practices of teaching, research and extension, and consequently is reflected in the acceptance in the world work, creating student employability, even before the end of the course, and good post-graduate pass rates, that cannot be measure by indicators.